Welcome to fairyland : queer Miami before 1940 - Capó, Julio, Jr (University of North Carolina Press, 2017)
"Poised on the edge of the United States and at the center of a wider Caribbean world, today's Miami is marketed as an international tourist hub that embraces gender and sexual difference. As Julio Capo Jr. shows in this fascinating history, Miami's transnational connections reveal that the city has been a queer borderland for over a century. In chronicling Miami's queer past from its 1896 founding through 1940, Capo shows the multifaceted ways gender and sexual renegades made the city their own. Drawing from a multilingual archive, Capo unearths the forgotten history of "fairyland," a marketing term crafted by boosters that held multiple meanings for different groups of people. In viewing Miami as a contested colonial space, he turns our attention to migrants and immigrants, tourism, and trade to and from the Caribbean--particularly the Bahamas, Cuba, and Haiti--to expand the geographic and methodological parameters of urban and queer history. Recovering the world of Miami's old saloons, brothels, immigration checkpoints, borders, nightclubs, bars, and cruising sites, Capo makes clear how critical gender and sexual transgression is to understanding the city and the broader region in all its fullness."--Back cover.
Keywords: Sexual minorities -- Florida -- Miami -- History -- 19th century.; Sexual minorities -- Florida -- Miami -- History -- 20th century.; Miami (Fla.) -- History -- 19th century.; Miami (Fla.) -- History -- 20th century.; Miami (Fla.) -- Race relations.; Caribbean Area -- Emigration and immigration.; Minorités sexuelles -- Floride -- Miami -- Histoire -- 19e siècle.; Minorités sexuelles -- Floride -- Miami -- Histoire -- 20e siècle.; Caraïbes (Région) -- Émigration et immigration.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Emigration and immigration; Race relations; Sexual minorities; Caribbean Area; Florida -- Miami; 1800-1999; History